Pine Forest Management and Disturbance in Northern Poland: Combining High-Resolution 100-Year-Old Paleoecological and Remote Sensing Data - Łuców, Dominika; Lamentowicz, Mariusz; Kołaczek, Piotr; Łokas, Edyta; Marcisz, Katarzyna; Obremska, Milena; Theuerkauf, Martin; Tyszkowski, Sebastian; Słowiński, Michał (Frontiers in Ecology and Evolution, 2021)
Global warming has led to the need to strengthen the resilience of European forests. Due to repeated droughts and heatwaves, weakened trees become vulnerable to insect outbreaks, pathogen invasions, and strong winds. This study, based on a 100-year-old high-resolution peat archive synthesized from the Martwe peatland and remote sensing data. We present the first REVEALS based vegetation reconstruction in a Tornado-hit area from Poland on the background of previous forest management in monocultural even-aged stands—Tuchola Pinewoods. During the 20th century, the area surrounding this peatland was affected by the abrupt deforestation of pine monocultures caused by both clear-cutting and insect outbreaks. In 2012, a tornado occurred, destroying ca. 550 ha of the forest area. Our study showed the strong relationships between the decrease of Pinus sylvestris (Scots pine) in palynological record and forest management as well as planting patterns after a tornado. Moreover, past forestry practices (such as domination of P. sylvestris, the collapse of Picea abies (Norway spruce), active removal of Betula (birch) as a “forest weed,” and low plant coverage of tree species due to clear-cutting and cutting after insect outbreaks) were well identified in the proxy record. In monocultures heavily exploited over decades, the reconstruction of vegetation may be challenging due to changes in the age composition of the P. sylvestris stands. We found that through historical, remote sensing, and paleoecological data, the dynamics of disturbances such as insect outbreaks and tornadoes, as well as the changing perceptions of local society about forests, can be determined. The size and setting of tree plantings is important to assess the land-use changes over the last century. We demonstrated the combination of paleoecological and historical data that is an important tool for ecosystem management to predict the future risks related to climate change and pathogen invasions.